2022
DOI: 10.1097/md.0000000000031048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of aqueous humor protein markers in different types of glaucoma

Abstract: To compare the concentrations of protein markers in aqueous humor (AH) of patients with primary open-angle glaucoma (POAG), chronic angle-closure glaucoma (CACG), acute primary angle closure (APAC), and cataract without glaucoma as the control group. AH samples were collected at the beginning of surgery from 82 eyes of 82 patients who were divided into POAG (n = 23), CACG (n = 21), APAC (n = 19), and cataract groups (n = 19). The expression levels of interferon-gamma (IFN-γ), interleukin-2 (IL-2), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, it is unclear whether this study's findings represent part of the pathogenesis of disease or the consequences of chronic IOP elevation, vascular dysregulation, inflammation, or other changes accompanying CPACG 1 . Interestingly, however, recent work in people has demonstrated that AH from individuals with both acute and chronic angle closure contains similar levels of MMPs and TIMPs (and that these levels are elevated in comparison with normal eyes or eyes with POAG) 70 . Regardless of their cause, findings of the current study may provide justification for sampling of dogs in earlier stages of disease and may also contribute to the development of new therapies for dogs with CPACG in later stages of disease.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Therefore, it is unclear whether this study's findings represent part of the pathogenesis of disease or the consequences of chronic IOP elevation, vascular dysregulation, inflammation, or other changes accompanying CPACG 1 . Interestingly, however, recent work in people has demonstrated that AH from individuals with both acute and chronic angle closure contains similar levels of MMPs and TIMPs (and that these levels are elevated in comparison with normal eyes or eyes with POAG) 70 . Regardless of their cause, findings of the current study may provide justification for sampling of dogs in earlier stages of disease and may also contribute to the development of new therapies for dogs with CPACG in later stages of disease.…”
Section: Discussionmentioning
confidence: 73%
“…1 Interestingly, however, recent work in people has demonstrated that AH from individuals with both acute and chronic angle closure contains similar levels of MMPs and TIMPs (and that these levels are elevated in comparison with normal eyes or eyes with POAG). 70 Regardless of their cause, findings of the current study may provide justification for sampling of dogs in earlier stages of disease and may also contribute to the development of new therapies for dogs with CPACG in later stages of disease. For example, elucidating changes in AH in later stages of disease could lead to improved outcomes for glaucoma filtration surgeries in later-stage patients, since failure of filtering blebs may be linked to constant exposure to profibrotic mediators like TIMPs in glaucomatous AH.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Subsequently, several studies reported abnormalities in serum cytokines, antibodies, and complement systems, and found that cytokine-mediated immune and inflammatory responses play an important role in the process of glaucomatous optic neuropathy. Notably, the aqueous humor of patients with glaucoma has higher concentrations of cytokines, such as IL-4, IL-6, IL-8, IL-10, vascular endothelial growth factor, and interferon-α, compared to healthy individuals ( 11 , 12 ). Yin ( 13 ) found that the levels of tumor necrosis factor-alpha (TNF-α) and transforming growth factor -β2 were significantly higher in the aqueous humor of patients with POAG than in those of patients with cataract.…”
Section: Discussionmentioning
confidence: 99%